Shanghai international consensus on diagnosis and comprehensive treatment of colorectal liver metastases (version 2019). Issue 6 (June 2020) - ; Zhou, Aiping; Parvaiz, Amjad; Zhu, Andrew; Eng, Cathy; Lau, Chi-wai; Song, Chun; Tang, Chung-ngai; Lynch, Craig; Wan, Desen; Loyer, Evelyne; Aucejo, Federico; et al.
Abstract: The liver is the most common anatomical site for hematogenous metastases from colorectal cancer. Therefore effective treatment of liver metastases is one of the most challenging elements in the management of colorectal cancer. However, there is rare available clinical consensus or guideline only focusing on colorectal liver metastases. After six rounds of discussion by 195 clinical experts of the Shanghai International Consensus Expert Group on Colorectal Liver Metastases (SINCE) from 29 countries or regions, the Shanghai Consensus has been finally completed, based on current research and expert experience. The consensus emphasized the principle of multidisciplinary team, provided detailed diagnosis approaches, and guided precise local and systemic treatments. This Shanghai Consensus might be of great significance to standardized diagnosis and treatment of colorectal liver metastases all over the world.